Vliv tlaku použitého při výrobě elektrod na jejich výsledné vlastnosti - Foltová, Anežka (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2017)
Tato diplomová práce se zabývá vlivem tlaku použitého při výrobě elektrod na jejich výsledné vlastnosti. V teoretické části práce jsou popsány sekundární elektrochemické zdroje, se zaměřením na Li-ionové akumulátory. Hlavní částí práce je praktická výroba Li-ionových akumulátorů za použití rozdílného lisovacího tlaku. Vlastnosti těchto článku jsou poté zkoumány pro určení optimálního lisovacího tlaku.

The aim of this work is to describe final properties of the electrodes based on the amount of pressure used during its production. In the theoretical part of this work, secondary electrochemical accumulators are described, with the focus on Li-ion accumulators. In the main part of this work, the production of Li-ion accumulators, with usage of different pressures during its production is described. In the final part of this work, the examination of these created cells for the classification of the optimal production pressure is described.
Effect of the pressure used in the manufacture of the electrodes on their final properties
Keywords: Akumulátor; Li-ion akumulátor; materiály kladné a záporné elektrody; lisovací tlak; Batteries; Li-ion batteries; materials of the positive and negative electrodes; pressure